Investigating vegetable contamination in indigent communities by heavy metals: a case of food safety in Bushenyi, Uganda. Issue 1 (1st January 2021) - Otim, Eric Oloya; Kasozi, Keneth Iceland; Zirintunda, Gerald; Matama, Kevin; Otim, Ochan
ABSTRACT: Food contamination by heavy metals is a health burden in sub-Saharan Africa. Here, we illustrate this burden by quantifying levels of Cd, Cr, Ni, Co, Pb, Fe, Cu and Zn in vegetables from Bushenyi District (Uganda). Results show that cabbage, scarlet eggplant, tomato and amaranth sold in Bushenyi, Ishaka, Kashenyi, Kizinda and Nyakabirizi open markets contain high levels of Zn and Fe. The uptake of metals overall appeared to be species-specific. Amaranth, for example, had more metals than scarlet eggplant, which in turn had more metals than tomato or cabbage. Within a species, cabbage from Ishaka and Kashenyi presented a combinatorial set of characteristics quite distinct from cabbage from other areas. Such differences arose perhaps from differential capacities to uptake/retain metals from soil or atmospheric particulates. More studies are needed to pinpoint sources of vegetable contamination in Bushenyi. Perhaps then remedial measures can be proposed.